PHYSICAL EDUCATION AND HIGH SCHOOL'S CURRICULUM (Fiep Bulletin - online, 2016)
This research aims to analyze the guidelines, guidelines and curriculum frameworks related to the teaching of Physical Education in public high schools in the state of Maranhão. The study seeks to provide a historical account of the methodology of teaching physical education and also as pedagogical guidelines related to the school curriculum include surpassing the critical and emancipatory critical approaches. The research appears as a case study, specifically, the Pedagogical Meeting of the Centro de Ensino Inácio Passarinho, in Caxias Maranhão state, occurred between days 27 and 28 February 2014, it was possible to understand that the overlapping between development, implementation and evaluation of the curriculum still requires reflections that relate to a more pedagogical do oriented to social, cultural and political reality of Maranhão State.
Keywords: Curriculum. Education. Physical Education.